Cancer and COVID-19: Currently in race for the title of “The Emperor of All Maladies!” - Jyoti Wadhwa; Aniket Saigal (Indian Journal of Medical and Paediatric Oncology)
Cancer has been the undisputed “Emperor of All Maladies” till now. The current COVID-19 pandemic has created havoc and seems to have displaced cancer from this notorious title. This narrative examines the facts and figures that have led to this succession.